Digitalization of The Fisherman Community in Taipa Hamlet, Takalar Regency - Rasyid Ridha,; Khaeruddin,; Zulfadli Tahir,; Ulul Azmi Mustari, (Technium Social Sciences Journal, 2023)
In order to promote the economic well-being of fishing villages in Taipa Hamlet, Takalar Regency, this study attempts to ascertain the circumstances, digitization efforts, and the government's significant role in their achievement. With qualitative descriptive data analysis, this study is qualitative in nature. According to research findings, the Taipa Hamlet fishing community is made up of people who are between 20 and 60 years old and is divided into three groups based on capital ownership: skipper fishermen, working fishermen, and owner fishermen. The issue that these groups face is the low selling price of the catch because of the direct marketing process. In Taipa Hamlet, Takalar Regency, there are a number of digitalization initiatives that can be implemented to enhance the economic well-being of the local fishing villages. These initiatives include the introduction of technology, instruction in its use, and testing of the technology that will be put to use. As the custodian of the reins of power, the government may play a significant part in accelerating the digitization of fisherman in Taipa Hamlet, Takalar Regency. Increasing people's access to technology is one of them.